2022
DOI: 10.1007/s12035-022-02772-z
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Degradation of Cortical Perineuronal Nets Reverses GABAergic Interneuron Maturation

Abstract: Perineuronal nets (PNNs) are specialised extracellular matrix structures which preferentially enwrap fast-spiking (FS) parvalbumin interneurons and have diverse roles in the cortex. PNN maturation coincides with closure of the critical period of cortical plasticity. We have previously demonstrated that BDNF accelerates interneuron development in a c-Jun-NH2-terminal kinase (JNK)–dependent manner, which may involve upstream thousand-and-one amino acid kinase 2 (TAOK2). Chondroitinase-ABC (ChABC) enzymatic diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 141 publications
(191 reference statements)
2
10
0
Order By: Relevance
“…One of underlying mechanisms seems to be mediated by the reduction in expression of PV and Kcnc1/Kv3, the potassium channels important for fast-spiking of PV neurons. Previous studies have reported similar changes after PNN degradation by chondroitinase ABC (Willis et al, 2022;Lupori et al, 2023).…”
Section: Ncan Depletion Increases Neuronal Activitysupporting
confidence: 70%
“…One of underlying mechanisms seems to be mediated by the reduction in expression of PV and Kcnc1/Kv3, the potassium channels important for fast-spiking of PV neurons. Previous studies have reported similar changes after PNN degradation by chondroitinase ABC (Willis et al, 2022;Lupori et al, 2023).…”
Section: Ncan Depletion Increases Neuronal Activitysupporting
confidence: 70%
“…Depletion of CSPGs in the adult brain by enzymatic degradation or genetic inhibition has been shown to promote plasticity. [72][73][74] CSPGs can also act as potent inhibitors of myelination, axon guidance and regeneration, and other injury repair processes. Further work is needed to determine the clinical relevance of CSPGs in myelin recovery after perinatal WMI.…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark cellular feature associated with the closure of critical periods is the deposition of PNNs ( Pizzorusso et al, 2002 ), which are lattice-like, proteoglycan-rich, ECM structures that coalesce around specific neuronal populations, in particular PV + inhibitory interneurons, and are linked to the limiting of neuronal plasticity in mature neuronal networks ( Bozzelli et al, 2018 ; Sigal et al, 2019 ; Willis et al, 2022 ). Prior evidence indicates that pharmacological antidepressants reopen “critical period-like plasticity” in adulthood, likely via the recruitment of Tropomyosin receptor kinase B (TrkB) signaling in PV + interneurons ( Maya Vetencourt et al, 2008 ; Guirado et al, 2014 ; Lesnikova et al, 2021 ; Mukhopadhyay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%